Interdisciplinary views of dental surgeon enrolled in the residency program in Primary Health Care in the municipality located in South region of Brazil (Research, Society and Development, 2022)
The Multiprofessional Residency Programs in Family Health, in an interdisciplinarity focused pedagogical model, favor the articulation between educational institutions and healthcare services, through the insertion of professionals into the multidisciplinary teams of Primary Health Care. This experience report intends to address the humanist and integrative role of the general dentist resident in the development of a multiprofessional and interdisciplinary work. The residents work in partnership with the Family Health teams and take part in activities alongside the Municipal Health Department. Additionally, the advent of the COVID-19 pandemic brought along resignification of health promotion and prevention concepts with greater integration of professionals. Thus, it highlights the formation process in which they are immersed, constructed by daily disciplines that develop their working skills, in conjunction with other health professionals and, consequently, also collaborate with the qualification of the Health Unic System services.